MODEL BIMBINGAN KONSELING PERKEMBANGAN DALAM AKTIVITAS BERMAIN SEBAGAI STRATEGI PENGALAMAN BELAJAR YANG BERMAKNA DI SD MUHAMMADIYAH 8 BANJARMASIN - Rizqi Amalia Aprianty; Ngalimun Ngalimun (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2022)
The structure of the developmental guidance and counseling program consists of four components, namely: First, basic guidance services (guidance curiculum), which is the core of the developmental guidance model. This component is designed to assist all students in developing basic skills or competencies in effective life and behavior. Second, responsive service aims to intervene in student problems or concerns that arise immediately and are felt at that time. Third, individual planning system (individual planning), aims to guide all students to learn to plan, monitor, and manage education and career plans. Fourth, equipped with a system support component, this component provides support for the guidance staff in organizing the three components of guidance as well as other school personnel in implementing educational programs in schools.Keywords: Developmental counseling guidance model, play activities, meaningful experience strategies